"That’s my Auntie": Community-Guided Residential School History - McCracken, Krista; Hogan, Skylee-Storm (KULA)

(untitled) (University of Victoria Libraries, 2021)
The Truth and Reconciliation Commission of Canada called for increased access to archival material documenting the history of Residential Schools. What does this access and associated programming look like? How can archives approach sharing Residential School history in an ethical and culturally appropriate way? This project report provides examples of reciprocal approaches to archival work by drawing on a case study of the community-guided work undertaken by the Children of Shingwauk Alumni Association (CSAA) and the Shingwauk Residential Schools Centre (SRSC).